2023
DOI: 10.1021/acsmedchemlett.3c00118
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Deoxygenative C(sp2)-C(sp3) Cross-Coupling for Parallel Medicinal Chemistry

Wei Liu,
James Mulhearn,
Bo Hao
et al.

Abstract: Herein we report the development of an automated deoxygenative C(sp 2 )-C(sp 3 ) coupling of aryl bromide with alcohols to enable parallel medicinal chemistry. Alcohols are among the most diverse and abundant building blocks, but their usage as alkyl precursors has been limited. Although metallaphotoredox deoxygenative coupling is becoming a promising strategy to form C(sp 2 )-C(sp 3 ) bond, the reaction setup limits its widespread application in library synthesis. To achieve high throughput and consistency, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In recent years, there has been significant expansion in the number and variety of methods for the formation of C­(sp 2 )–C­(sp 3 ) bonds using transition metal-catalyzed cross-coupling . A major driver for the development of new C­(sp 2 )–C­(sp 3 ) bond-forming reactions is their high interest to medicinal chemists . The products of such reactions have a higher fraction of sp 3 carbon atoms (Fsp 3 ) than those of more traditional cross-couplings, and higher Fsp 3 has been correlated with improved physicochemical properties and increased “drug-likeness” .…”
mentioning
confidence: 99%
“…In recent years, there has been significant expansion in the number and variety of methods for the formation of C­(sp 2 )–C­(sp 3 ) bonds using transition metal-catalyzed cross-coupling . A major driver for the development of new C­(sp 2 )–C­(sp 3 ) bond-forming reactions is their high interest to medicinal chemists . The products of such reactions have a higher fraction of sp 3 carbon atoms (Fsp 3 ) than those of more traditional cross-couplings, and higher Fsp 3 has been correlated with improved physicochemical properties and increased “drug-likeness” .…”
mentioning
confidence: 99%
“…These collaborations can leverage the “know-how” and innovation of academia and the state-of-art facilities, capabilities, and synthetic problems from industry to result in synthetic methods where the product is greater than the sum of its parts. Industrial teams have also helped to advance this field and examples include recent studies on method validation for both medicinal chemistry and process chemistry applications. ,,, Finally, with the fast adoption of photoredox cross-couplings in medicinal chemistry projects, the necessity of large-scale syntheses utilizing this chemistry for drug candidates, or their intermediates, will be inevitable. Some aspects revolving around scalability remain to be addressed, despite the great progress that has been made in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The most recently published of the four transformations evaluated in this study was the deoxygenative coupling, first shown by MacMillan and co-workers in 2021 . This transformation was rapidly adopted internally for analogue synthesis, and on the basis of recent reports, other pharmaceutical companies have embraced this method, too . The major disadvantage of this protocol compared to the others is the requirement of a two-step process: activation of the alcohol using a benzoxazolium N -heterocyclic carbene (NHC) reagent followed by a nickel/photoredox-catalyzed cross-coupling of the activated alcohol with an aryl halide substrate.…”
Section: Developing Internal Expertise Through a Systematic Compariso...mentioning
confidence: 99%
See 2 more Smart Citations